2011
DOI: 10.1155/2011/652097
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Nuclear FactorκB in Diabetic Cardiomyopathy

Abstract: Diabetic cardiomyopathy entails the cardiac injury induced by diabetes independently of any vascular disease or hypertension. Some transcription factors have been proposed to control the gene program involved in the setting and development of related processes. Nuclear factor-kappa B is a pleiotropic transcription factor associated to the regulation of many heart diseases. However, the nuclear factor-kappa B role in diabetic cardiomyopathy is under investigation. In this paper, we review the nuclear factor-kap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
112
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(116 citation statements)
references
References 67 publications
(117 reference statements)
4
112
0
Order By: Relevance
“…It is known that NF-B activation is a key event for the initiation of cardiovascular pathogenesis in diabetes as a result of increased oxidative stress (56,57). We found that the protein levels of the NF-B1/p50 and p65 subunits were augmented in diabetic vessels and in HG-cultured human coronary SMCs.…”
Section: Discussionmentioning
confidence: 61%
“…It is known that NF-B activation is a key event for the initiation of cardiovascular pathogenesis in diabetes as a result of increased oxidative stress (56,57). We found that the protein levels of the NF-B1/p50 and p65 subunits were augmented in diabetic vessels and in HG-cultured human coronary SMCs.…”
Section: Discussionmentioning
confidence: 61%
“…Much of the inflammatory response in diabetic cardiomyocytes is attributed to activation of the transcription factor NF‐κB by elevations in ROS,113 although increased levels of cytokines, chemokines, adhesion molecules and infiltrating leucocytes are also important in this process. In experimental STZ‐induced T1D models of diabetic cardiomyopathy, NF‐κB activation was shown to be correlated with the increased release of IL‐1β and TNF‐α 113, 114, 115. Moreover, elevated levels of these two pro‐inflammatory cytokines have been found in the circulation and hearts of patients with T2D 116.…”
Section: Diabetic Cardiomyopathy Antioxidant Defences and Immunothermentioning
confidence: 99%
“…Moreover, elevated levels of these two pro‐inflammatory cytokines have been found in the circulation and hearts of patients with T2D 116. In fact, several studies report a strong correlation between the characteristic hallmarks of diabetic cardiomyopathy and the levels NF‐κB and cytokines 113. It should be noted that cardiomyocytes and fibroblasts express receptors for IL‐1β and TNF‐α.…”
Section: Diabetic Cardiomyopathy Antioxidant Defences and Immunothermentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical and experimental studies have shown that inflammatory reactions possibly play an important role in the development of diabetic cardiomyopathy (DC) (Dasu et al, 2008;Jiao et al, 2009;Van Linthout et al, 2007;Westermann et al, 2009;Lorenzo O et al, 2011). Nuclear factor-kappa B (NF-κB) is the key factor in the inflammation signal pathway.…”
Section: Introductionmentioning
confidence: 99%